Learning Telenursing Online using Role-Playing Simulations-Advanced Practice Nursing Students’ Experiences - Salminen-Tuomaala, Mari; Perälä, Sami (International Journal of Educational Studies, 2025)
High-technology simulations and standardized patients are costly and require training. Online role playing simulations represent a simple, hands-on learning approach. Data was collected from 28 advance practice nursing students. The results are based on students’ responses to open questions on their experiences of online role-play simulations, analyzed using inductive content analysis. The participants considered online role-play simulations effective; they appreciated the hands-on experience of the technology, observing the performance of other students and shared reflection. Their development proposals involved adding elements of surprise into the simulations, random ready-made roles and a wider range of technology. Online role-play simulations provide a practical, cost-effective method to practice theoretical and practical competencies required in telenursing.